(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Water wise use and conservation is one of the key prerequisites for economic sustainable development. Accession to the European Union, Latvia is committed to meeting the EU environmental requirements. Water Framework Directive (Directive 2000/60/EC, 2000) is a legal act, which provides water protection and sustainable management principles and tasks of the European Union. It provides uniform protection and management system for all waters: rivers, lakes, coastal waters and groundwater, providing that they must also achieve good water quality by 2015. year. The Directive provides for the identification of the current water situation and to obtain additional information by following the water monitoring and for basic background information to establish an action program to improve water quality. Therefore, the Latvian conditions are important to assess the flow of nutrients, their sources and amounts of Latvian detention basins using existing models and innovations in methods and model systems for the retention of part of the calculation. Therefore, in this publication are offered in various countries of the world models will be useful in Latvian processing of data.